Socialization Towards Internationalization: Survey Research on University Students in China - Ren, Zheng; Wang, Fei (Journal of International Students, 2021)
Although students are the main recipients of internationalization in higher education (IHE), research on IHE mainly focuses on particular nations or educational institutions rather than the individual. Perceptions of university students towards internationalization, particularly what may impact their preparedness for and critical awareness of internationalization are largely lacking. This study explores in what ways students’ diverse socialization or experiences of socializing with different stakeholder’s impact their preparedness for and awareness of increasing internationalization in higher education institutions. The study utilizes data from a survey conducted with 511 students at two Chinese universities. The study found that students with diverse socialization backgrounds are more likely to develop a critical awareness of the social impact of internationalization, and that they believe internationalization enables them to learn from others, to develop capacities to analyze global issues, to develop skills to work with cultural others, and to make ethical decisions on social issues.